Molecular Mechanisms of Anti-cancer Activities of β-elemene: Targeting Hallmarks of Cancer - Jiang, Shiyu; Ling, Chunhua; Li, Wei; Jiang, Hongxin; Zhi, Qiaoming; Jiang, Min (Anti-Cancer Agents in Medicinal Chemistry, 2016)
Increasing knowledge on the hallmark characteristics of cancer and tumor pharmacology has promoted the introduction of phytochemicals, such as traditional Chinese medicine (TCM) in cancer therapy, which modulate numerous molecular targets and exert anticancer activities. β-elemene, an active and non-toxic compound isolated from the Chinese medicinal herb Rhizoma Zedoariae, has been explored as a potent anti-cancer agent against multiple cancers in extensive clinical trials and experimental research in vivo and in vitro. β-elemene exerts therapeutic potential via modulation of core hallmark capabilities of cancer by suppressing proliferative signaling, such as MAPK and PI3K/Akt/mTOR pathway, inducing cell death, up-regulating growth suppressors, deactivating invasion and metastasis and interacting replicative immortality and attenuating angiogenesis. Recent studies have significantly improved our understanding of anti-cancer activities and underlying molecular mechanisms of this Chinese medicine. This review presents these novel findings regarding the unique properties of β-elemene as an agent for cancer treatment, with an emphasis on multi-targeting biological and molecular regulation.
Keywords: anti-cancer activity